"Rock-a-Bye, Baby!": Black Women Disrupting Gangs and Constructing Hip-Hop Gangsta Films - Smith-Shomade, Beretta E. (Cinema Journal, 2003)
This essay examines the cultural specificity of the gangster genre. In hip-hop gangsta films, the inclusion of black women as central to the gangster business not only transforms the gangster genre but, more important, adheres to black cultural norms. The films New Jack City, Sugar Hill, and Set It Off serve as case studies.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé